2009
DOI: 10.1007/s12032-009-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume increase after tamoxifen, but not after anastrazole in adjuvant therapy of breast cancer

Abstract: We found increased MPV after tmx treatment, but did not after anastrazole treatment. The advanced studies which explore biological significance of high MPV in breast cancer patients used endocrine therapy, should be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Large platelets are more reactive than their smaller counterparts, and are more likely to aggregate, leading to thrombosis. Large platelets are an independent risk factor for myocardial infarction, as platelet size is a predictor of recurrent myocardial infarction and death ( 14 ). The MPV tested in our study can be easily evaluated by hematological analyzers, which makes it a convenient marker of platelet functions and activation ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large platelets are more reactive than their smaller counterparts, and are more likely to aggregate, leading to thrombosis. Large platelets are an independent risk factor for myocardial infarction, as platelet size is a predictor of recurrent myocardial infarction and death ( 14 ). The MPV tested in our study can be easily evaluated by hematological analyzers, which makes it a convenient marker of platelet functions and activation ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the larger PLTs are more reactive than the smaller ones and are more likely to aggregate, leading to thrombosis. Large PLTs (LPLTs) are independent risk factors for myocardial infarction, and PLT size is one predictor of recurrent myocardial infarction and death ( 19 ). A high level of MPV, a marker of PLT size, may indicate tendency towards thrombosis, and has been demonstrated in the case of myocardial infarction and cerebrovascular embolus ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 There is little information available about the value of MPV on risk prediction and data on the effects of chemotherapy on this platelet index are contradictory. Indeed, MPV has been reported to increase after tamoxifen adjuvant therapy of breast cancer patients 7 which led some authors to solicit studies to assess the need and timing of anti-platelet drugs if elevated MPV is found in tamoxifen-treated patients. 8 On the other hand, MPV was significantly reduced by antiangiogenic treatment of metastatic colon cancer, a condition known to increase thromboembolic risk.…”
Section: Introductionmentioning
confidence: 99%